(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Fire can be classified as an accidental or natural occurrence, but if someone deliberately sets fire on someone’s property, it becomes a crime of arson. Arson is a deliberate or willful setting of fire through property and is still a major issue on a global scale, resulting in high costs of damage in terms of property loss, injuries, and fatalities. The purpose of this study is to assess the effectiveness of arson investigation in Barangay 171 North Caloocan. The results of the study about the effectiveness of arson investigation in barangay 171 North Caloocan indicate that the effectiveness of arson investigation is based on the sufficient numbers of arson investigators assigned to arson investigation, which garnered the most response from the respondents with the weighted mean of 3.70 and with the verbal interpretation of “Strongly Agree”. The researchers suggest measures that can be proposed to address the problem encountered.